(untitled) (Journal of Philosophy Culture and Political Science, 2023)
The philosophy of independent living is an important and key element in contemporary public discourse, permeating various aspects of our lives. It represents not just a set of principles and ideas but reflects fundamental rights and values that should be accessible to every individual, regardless of their physical, psychological, or cognitive characteristics. At the core of the philosophy of independent living lies an inclusive approach. Inclusivity envisions a society in which everyone, regardless of nationality, physical or intellectual abilities, social background, feels valued, fully integrated, and has equal opportunities. One of the fundamental principles in implementing the concept of inclusivity is the accessibility and equality of education. Undoubtedly, the integration of individuals with special educational needs (SEN) into the education system is a central topic in the global dialogue on the issues facing people with disabilities. To overcome the social barriers they encounter, it is necessary to provide not only physical adaptations such as ramps, specialized equipment, and trained personnel but also a change in societal attitudes. This is not just a matter of charity, it is a matter of protecting their rights. To realize these rights, comprehensive support from the government and society is required, including the enactment of appropriate legislation, the development of social infrastructure, digitalization of society, and more. However, despite widespread coverage and the interest of the global scientific community in this issue, there is a substantial difference in the level and quality of research in various countries. In an attempt to assess the state of inclusive education in Kazakhstan, the authors conduct a comprehensive review and analysis of contemporary scientific research in the chosen field conducted by domestic scholars. Keywords: special educational needs, inclusiveness, limited health capabilities, education, independent life, philosophy.